Enhancedanti-tumor efficacy through a combination of intramuscularly expressed DNA vaccine and plasmid-encoded PD-1 antibody - Xun Liu; Yueyao Yang; Xiufeng Zheng; Ming Liu; Gang Wang (Frontiers in Immunology, 2023)
Immune check inhibitors (ICIs) have moderate response rates (~20%–30%) in some malignancies clinically, and, when used in combination with other immunotherapeutic strategies such as DNA tumor vaccines, there is evidence to suggest that they could optimize the efficacy of cancer treatment. In this study, we validated that intramuscular injection of plasmid DNA (pDNA) encoding OVA combined with pDNA encoding α-PD-1 (abbreviated as α-PD-1 in the following treatment groups) may enhance therapeutic efficacy by means of in situ gene delivery and enhanced muscle-specific potent promoter. Mice treated with pDNA-OVA or pDNA-α-PD-1 alone showed weak tumor inhibition in the MC38-OVA-bearing model. In comparison, the combined treatment of pDNA-OVA and pDNA-α-PD-1 resulted in superior tumor growth inhibition and a significantly improved survival rate of over 60% on day 45. In the B16-F10-OVA metastasis model, the addition of the DNA vaccine enhanced resistance to tumor metastasis and increased the populations of CD8+ T cells in blood and spleen. In conclusion, the current research shows that a combination of pDNA-encoded PD-1 antibody and DNA vaccine expressed in vivo is an efficient, safe, and economical strategy for tumor therapy.